BANI SALJUK DAN KEBANGKITAN PERADABAN DAULAH ABBASIYAH - Mundzirin Yusuf (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2013)
Saljuqs is derived from the family of the tribe of Oghuz Qiniq inTurkish society , that their residence in the Steppes (north of the Caspian and Aral Sea). For various reasons -among - economic problems of their journey to the west ( Anatoli / Asia Minor ). In groups , they left their homeland to seek a better life . As life provision , they rob , destroy houses , markets , asking savings (savings possessions ) causing chaos , and war . Bani Saljuq appearance in 447/1055 in the capital of the caliphs of Baghdad, freeing sectarian religious pressure . Initially , Bani Saljuq - despite having a strong Sunni - view does notintend to let the rise of political power equally caliph of Sunni . However, in the twelfth century Saljuq Kingdom / Great show their solidarity and their power becomes weak , the fate of the Abbasid Daula was starting to improve . At the time of Caliph al - Qa ` im who ruled in 422-467/1031-1074 , have recourse to Amir Toghrul Bik / Toghril Bik based in Nishapur to liberate Bani Buwaih power pressure , then Amir Toghril Bik action . In 1055, Toghril master control of Bani Baghdad that ended the Abbasid Daula Buwaih above . Subsequently , in 1057 , Toghril seize Mosul , Diyarbakr , and Nissibin . In fact , the rulers of these areas want to break free from central government ( Baghdad ) . In 1063, ToghrilMalik died and was replaced by Alp Arselan , and the replacement Toghrilcompetent caliphs , the Abbasid Daula flag was hoisted again . Emergence of the Turkish dynasty in the eleventh century and later became the builder of Islamic civilization , the results of which can still be seen today. Their relationship is not limited to politics alone , but rather reinforced melelui marriage between Daula Abbasid ruler with family SaljuqsKeywords: Bani Saljuk, Daula Abbasid, Islam History